(untitled) (JBN (Jurnal Bedah Nasional), 2026)
Background: Post-burn contracture (PBC) of the neck is one of the most common burn sequelae and may cause restriction of neck movement and mouth closure, breathing difficulties, and cosmetic disfigurements, making its management a challenging surgical procedure. Case: Two patients, a 37-year-old female and a 14-year-old male, presented with difficulty in straightening the neck and were diagnosed with post-burn mentosternal contracture Onah classification type III; both underwent contracture release and defect reconstruction using anterolateral thigh (ALT) flap with defect sizes of 10 cm x 8 cm on the right side and 15 cm x 8 cm on the left side, elevated 1–5 mm. The surgeries went uneventful and, at one-month follow-up, both patients showed increased neck mobility with viable flaps. Conclusion: The aims of contracture release and reconstruction in PBC are to restore cervical mobility and improve appearance, and ALT flap represents an excellent option that provides good pliability, thin skin, less hair, good donor-site recovery, acceptable skin color match, minimal donor-site morbidity, and an adequate amount of tissue to cover large post-release defects when local flaps are unavailable or suboptimal due to burn injury.